Electrical Circuit Modeling of Nanofluidic Systems - Sebastian, John; Green, Yoav (Advanced Physics Research, 2023)
Nanofluidic systems exhibit transport characteristics that have made technological marvels such as desalination and energy harvesting possible by virtue of their ability to influence small currents due to selective ion transport. Traditionally, these applications have relied on nanoporous membranes whose complicated geometry impedes a comprehensive understanding of the underlying physics. To bypass the associated difficulties, we consider the simpler nanochannel array and elucidate the effects of interchannel interactions on the Ohmic response. It is demonstrated that a nanochannel array is equivalent to an array of mutually independent but identical unit‐cells whereby the array can be represented by an equivalent electrical circuit of resistances connected in a parallel configuration. The model is validated using numerical simulations and experiments. The approach to modeling nanofluidic systems by their equivalent electrical circuit provides an invaluable tool for analyzing and interpreting experimental measurements.